Risk factors for social withdrawal in amyotrophic lateral sclerosis/motor neurone disease. Issue 7 (2nd October 2018) - Schlüter, Daniela K.; Tennant, Alan; Mills, Roger; Diggle, Peter J.; Young, Carolyn A.
Abstract: Background: Greater social withdrawal is related to higher levels of psychological distress and poorer adaptation to a diagnosis of amyotrophic lateral sclerosis. Objectives: To examine whether demographics and functional deficits can be used to assess which patients may be at risk of social withdrawal and whether symptoms including depression and anxiety can provide additional information for identifying individuals at risk. Furthermore, to examine whether patient-perceived stigma has a role in mediating the effects of any of the predictors of social withdrawal. Methods: A total of 559 participants in the ongoing Trajectories of Outcomes in Neurological Conditions (TONiC) study completed a questionnaire pack collecting data on demographics and a range of patient reported measures. Multiple regression analysis was employed to assess associations of functional ability, demographics, physical symptoms, anxiety, and depression with social withdrawal. The mediating role of stigma was assessed through the development of a bivariate linear regression model for stigma and social withdrawal. Results: Disability in the bulbar and motor domains, anxiety and depression were found to be significant predictors of social withdrawal. Stigma was the strongest single predictor of social withdrawal and was found to partially mediate the effects of functional deficits and mood on social withdrawal. Conclusions: Social withdrawal is associated with worse motor disability and poorer bulbar function, as well as increased anxiety and depression. Stigma is a powerful predictor for social withdrawal; further work should investigate whether stigma is a potential target for psychological interventions aimed at reducing social withdrawal and improving quality of life.